User-generated content: an examination of users and the commodification of Instagram posts - Macon, June Mia, author; Martey, Rosa Mikeal, advisor; Abrams, Katherine, committee member; Garcia, Antero, committee member (Colorado State University. Libraries, 2017)
The language around social media contributes to perceptions of who is posting content and why. The concept of user generated content (UGC) places an emphasis on authorship and has been defined as online content that is publically available and created by end-users in a creative effort (Dennhardt, 2013). UGC is a powerful tool for businesses because it taps into one of the most valued marketing tools: verbal consumer-to-consumer communication, which is also known as "word of mouth" (WOM) marketing. However, the tactics used by companies to integrate UGC with their own content and goals has resulted in a blurred line between sponsored content paid by advertisers and UGC independently posted by regular users. Recent attempts to regulate this distinction have struggled to determine how, exactly, audiences can be effectively alerted to paid content on social media platforms, especially Instagram. This study uses the persuasion knowledge model (PKM) as a theoretical framework to examine if and when audiences' responses to and coping mechanisms are triggered in Instagram. It argues that digital media literacy is especially challenged in UGC platforms, and draws on political economy to suggest that the relationships between producers and consumers has been blurred in favor of the producers. Online users who have a well-known or niche brand can make money from his or her brand and online community because companies use "regular people" to push products to reach a specific audience; one that a regular user has the ability to build and maintain. This is why businesses have targeted UGC and why the user interaction with this type of content needs to be re-examined. This study examines the relationships between viewer perceptions of commercial sponsorship and post content in the social media platform, Instagram. Specifically, it examines whether or not the trust and credibility generally associated with electronic word-of-mouth are affected by hashtags and other cues on Instagram posts. This project asks, Does the commodification of user-generated content change the way the content is perceived by users? It tests these relationships in an experiment that manipulates hashtags and @name text that accompany an image. The study hypothesizes that users will not be more likely to identify content as sponsored when a #promoted tag is present in the caption than when #ad or #sponsored is used; it also hypothesizes that @company_name tags were more likely to be recognized as sponsored than the hashtag text versions. Changes in advertising recognition, persuasive intent of the message, trust in the message, and credibility of the message were examined in between subjects' analyses using ANOVAs, correlations, and t-tests. The results revealed several findings. Results showed users recognized the @company_handle as an advertisement more than #ad, #sponsored, and #promoted. The results also showed no significant difference between user's perception of the hashtags #ad, #sponsored, and #promoted. Also, even when these cues were present, some participants were not aware of their presence and did not recognize any advertising on the post within the survey. It was also found that once identified as an advertisement, the trustworthiness and credibility towards the post was not affected.